Recruiting farm parents for a 6-week online child safety survey study using paid Facebook advertisements - Burke, Richard; Weichelt, Bryan P.; Namkoong, Kang; Ploeckelman, Melissa (Frontiers in Communication, 2023)
Agricultural populations are a popular target for research due to the industry’s dangerous conditions, unique work environments, and youth-including workforce. However, reaching and recruiting eligible participants is challenging and expensive when compared to other industries. We conducted a two-phase, multi-week paid advertising campaign on Facebook.com, varying delivery time, imagery, verbiage, and targeting methods to recruit U.S. farm parents for an online survey study investigating childhood agricultural safety. Advertisements were active for four weeks in fall 2021 and three weeks in winter 2022 at $1500 per week. The fall recruitment targeted farm parents, depicting three farm-related images, while the winter recruitment targeted all parents, depicting farm-rescue trainings with firefighters. The fall recruitment garnered 5,535 link clicks with a reach of 233,690 ($1.07 per click). The winter recruitment garnered 8,602 clicks with a reach of 750,764 ($0.53 per click) and higher user engagement. A total of 1,439 participants began the screener questionnaire, a conversion rate of 10.18%. Of 815 completed responses, 271 met our inclusion criteria. 164 participants completed the study: 45 from fall (27.6% dropout) and 119 (40% dropout) from winter. The overall attrition rate was 38.1% and cost per completed response was $64 USD. We successfully recruited our target sample size for this study. Notably, advertisement timing, imagery, and sampling frame likely affected performance. A screening questionnaire was imperative in identifying sham responses. These findings show that paid Facebook advertising can be a feasible recruitment tool to engage with a traditionally difficult to reach population with proper precautions and planning.